289 MRI abnormalities in mog antibody disease. Issue 10 (13th September 2018) - S, Huda; Al-Orainy, Amal; Saldanha, Anita; D, Whittam; Denby, Christine; Pandit, Lekha; M, Bhojak; A, Jacob
Abstract : Aims: To analyse the MRI abnormalities of myelin oligodendrocyte glycoprotein-antibody (MOG-Ab) associated demyelinating disease. Methods: Clinical records and 165 MRIs from 56 patients with MOG-Abs were reviewed. Results: The median age was 29(8–71) years and 52% percent were female. Common phenotypes included isolated optic neuritis (ON)=17, or transverse myelitis (TM)=16, ON+TM =12, and combinations of above groups with cerebral and/or brainstem involvement=11. Seventeen patients (30%) fulfilled NMOSD 2015 diagnostic criteria. All patients had brain imaging and 89% (50/56) had spinal imaging. Common areas of MRI brain abnormality involved brainstem(32%), hemispheric white matter(29%), corticospinal tracts(21%), and U-fibres(20%). Dawson's fingers were not detected in any patients. Cord imaging showed longitudinally extensive myelitis in 69% (20/29) and atrophy in 4% (2/47). Optic nerve imaging was abnormal in 69% (18/26) of patients, with bilateral lesions in 33% and long lesions (orbital and/or canalicular) in 83%. On serial MRI, radiological improvement was observed in 76% (22/29; median interval- 14 months) and importantly asymptomatic new lesions were absent in 13 untreated patients after a median of 16.5 months. Conclusions: Apart from optic nerve and spinal cord changes, brainstem and hemispheric white matter abnormalities are common in MOG-antibody disease. Irrespective of treatment, asymptomatic accrual of brain and/or spinal lesions is uncommon.